If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-1x)(-1x) + -3x + 10 = 0 Remove parenthesis around (-1x) -1x(-1x) + -3x + 10 = 0 Remove parenthesis around (-1x) -1x * -1x + -3x + 10 = 0 Reorder the terms for easier multiplication: -1 * -1x * x + -3x + 10 = 0 Multiply -1 * -1 1x * x + -3x + 10 = 0 Multiply x * x 1x2 + -3x + 10 = 0 Reorder the terms: 10 + -3x + 1x2 = 0 Solving 10 + -3x + 1x2 = 0 Solving for variable 'x'. Begin completing the square. Move the constant term to the right: Add '-10' to each side of the equation. 10 + -3x + -10 + x2 = 0 + -10 Reorder the terms: 10 + -10 + -3x + x2 = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -3x + x2 = 0 + -10 -3x + x2 = 0 + -10 Combine like terms: 0 + -10 = -10 -3x + x2 = -10 The x term is -3x. Take half its coefficient (-1.5). Square it (2.25) and add it to both sides. Add '2.25' to each side of the equation. -3x + 2.25 + x2 = -10 + 2.25 Reorder the terms: 2.25 + -3x + x2 = -10 + 2.25 Combine like terms: -10 + 2.25 = -7.75 2.25 + -3x + x2 = -7.75 Factor a perfect square on the left side: (x + -1.5)(x + -1.5) = -7.75 Can't calculate square root of the right side. The solution to this equation could not be determined.
| 3(4-4)=-6 | | x^3/4=5.2 | | 2y+3=5x+6 | | 2x+3=5y+6 | | -16t^2+64t+80=x | | 2x+2(-4x+4)=13 | | -2=-16t^2+31t+6 | | 17=-2x^3+3x | | xy-34=21 | | x=-4y-2 | | 64x^2+6=10 | | 5x=-2x+27 | | 4.4+1.5x=2.5x | | 6/8×2/7 | | 0=-16t^2+31t+4 | | 7x-15=8x+3 | | 6=-16t^2+31t+4 | | 0=-16t^2+31t+6 | | 8x-24=-6x | | 4=-16t^2+31t+6 | | ex=14 | | -9m^2+4m+8=0 | | (3*sinx)/2=0 | | 3sinx/2=0 | | 7x^2y+14x^2= | | -x+27x+28=0 | | 7/12y-1/4=2y-3/5 | | x-30=1/6 | | 6=-16t+31t+4 | | y+8=-5(x+9) | | 4=-16t+31t+6 | | 2/3x^-1/3=1 |